Implementation of K-Means Clustering to Human Development Indicators in East Nusa Tenggara - Simarmata, Justin Eduardo; Chrisinta, Debora; Purnomo, Miko (Journal of Research in Mathematics Trends and Technology, 2024)
K-Means has been adopted to group various cases related to the quality of human resources and economic growth. This study aims to apply K-Means to the characteristics based on selected Human Development Index (HDI) indicators, namely the average length of schooling, the expectation of length of schooling and life expectancy in Province of East Nusa Tenggara. The optimal cluster obtained is 6 clusters. The cluster with the highest average value of all variables is in cluster 1 which is Kupang City area. Meanwhile, condition cluster 6 provides the smallest life expectancy value compared to other clusters. The smallest average variable of school length is in cluster 2. The regions that provide the smallest number expectation of length of schooling is in cluster 5.